Twenty-one prophetic papers a suggestive outline of the whole range of God's dealings with the Jew, the Gentile and the Church of God - Bland, Frederick Christopher, 1826-1894 (London, UK Pickering and Inglis)
Includes bibliographical references.
Brethren writer
Keywords: Dispensationalism -- theology